Marketing of Moa buffalo at farm level in Maluku Province, Indonesia - Jomima Martha Tatipikalawan; F. T. Haryadi; E. Sulastri; T.S.M. Widi (Universitas Bengkulu, 2022)
Buffalo Moa is Indonesia's local livestock which is potentially maintained by the community on Moa Island as a source of family income and nutrition. This study aims to examine the marketing system, selling prices and factors that influence the price of buffalo at the farmer level. The results of the study found that the maintenance system was still traditionally carried out with two systems, namely semi-intensive during the rainy season and extensive during the dry season. The main motivation for raising livestock as a source of income, others as a means of payment for customary sanctions, family and religious events, marriage dowries. Buffalo cattle are marketed in the form of live animals and use intermediary traders. Weak market information so traders are more dominant in selling prices. Determination of the value of buffalo as a medium of exchange based on horn length and sex, the value of buffalo to be traded based on its performance, not defective, male sex at a higher price and the age range of 5–10 years, normal skin (not albino) is preferred Factors that influence the selling price at the breeder level are buffalo age, gender, skin color and climate.